B and T Cells Driving Multiple Sclerosis: Identity, Mechanisms and Potential Triggers - van Langelaar, Jamie; Rijvers, Liza; Smolders, Joost; van Luijn, Marvin M. (Frontiers in Immunology, 2020)
Historically, multiple sclerosis (MS) has been viewed as being primarily driven by T cells. However, the effective use of anti-CD20 treatment now also reveals an important role for B cells in MS patients. The results from this treatment put forward T-cell activation rather than antibody production by B cells as a driving force behind MS. The main question of how their interaction provokes both B and T cells to infiltrate the CNS and cause local pathology remains to be answered. In this review, we highlight key pathogenic events involving B and T cells that most likely contribute to the pathogenesis of MS. These include 1) peripheral escape of B cells from T cell-mediated control, 2) interaction of pathogenic B and T cells in secondary lymph nodes, and 3) reactivation of B and T cells accumulating in the CNS. We will focus on the functional programs of CNS-infiltrating lymphocyte subsets in MS patients and discuss how these are defined by mechanisms such as antigen presentation, co-stimulation and cytokine production in the periphery. Furthermore, the potential impact of genetic variants and viral triggers on candidate subsets will be debated in the context of MS.